How Macroeconomic Factors Affect Income Distribution : The Cross-Country Evidence - Sarel, Michael (IMF Working Papers; Working Paper, 1997)
This study develops a cross-section empirical framework to examine the relationship between the macroeconomic environment and trends in income distribution. The macroeconomic variables that are found to be associated with an improvement in income distribution are higher growth rate, higher income level, higher investment rate, real depreciation (especially for low-income countries), and improvement in terms of trade. The estimated significant effects of growth, income, and investment provide evidence that policies designed to promote investment and growth are likely also to contribute to an improvement in income distribution.